DEVELOPING CREATIVITY IN PRIMARY SCHOOL STUDENTS - Berdiqulova Buvraykhon Tolkynjon qizi (Bright Mind Publishing, 2025)
This article analyzes the pedagogical features of developing students' creative activity in primary education and its role in the educational process. The article discusses the main methods, principles, and techniques for fostering creativity. It emphasizes how encouraging creative thinking, considering individual student characteristics, and supporting their independent activities can enhance the effectiveness of education. The role of pedagogical innovations and modern methodological approaches in nurturing creativity is also explored. Furthermore, the article references normative documents such as the Law "On Education" of the Republic of Uzbekistan and the “National Training Program,” as well as reform measures aimed at improving the education system. This study provides valuable insights into pedagogical practices aimed at enhancing creative activity in primary education.
Keywords: Primary education, creative activity, pedagogical features, innovative approaches, creative thinking, independent activity, educational reforms, education in Uzbekistan, teaching methodologies, individual student characteristics.